An ab initio study of the influence of crystal packing on the host-guest interactions of calix[4]arene crystal structures - Ogden, Mark; Rohl, Andrew; Gale, Julian (The Royal Society of Chemistry, 2001)
We report the first quantum mechanical calculations of p-tert-butylcalix[4]arene inclusion complexes in the crystalline state with geometrical aspects demonstrating good agreement with experiment, while comparison of the configurations calculated for an isolated complex and in the crystal, illustrate that crystal packing forces contribute to the observed structure of the host–guest assembly.